FNCKING WITH WHITE FRAMES: TEEJAYX6 SCAM RAPS THE DIGITAL - Tynes, Robert; Pearl, Alex (AoIR Selected Papers of Internet Research, 2020)
Teejayx6 is a scam rapper from Detroit who puts to shame the notion that the internet is a cyberspace frontier where you can be all you wanna be. Instead, he presents it as a rich field to be harvested, and through his music provides insights about race and the internet. Ever since Kolko et al. (2000) published Race in Cyberspace, internet studies has tried to tease out how race plays out on the internet. But, as scholar Jessie Daniels (2012) shows, the field has come up way short. Maybe that’s because academics are too focused on what’s going on “in there” with race. There’s too much of a focus on the traditional analyses of representations of blackness, or of browness, or of yellowness. Instead, in line with Daniels (2012) urgings, we should be figuring out how whiteness is embedded, so deeply, in the internet. And so, we ask: What does Teejayx6’s scam rap, and the the scam rap of his predecessors, tell us about whiteness and the internet? Teejayx6 lyrics and online interviews help expose whiteness mythologies entrenched in internet discourse. We see how the open frontier of cyberspace masks territorialization; how identity fluidity is more of an elite fantasy than a pluralistic fact; and, how the promise of leisure and prosperity is false consciousness at best.